Sympathetic Solar Eruption on 2024 February 9 - Li, Shu-Yue; Zhang, Qing-Min; Ying, Bei-Li; Feng, Li; Su, Ying-Na; Lin, Mu-Sheng; Zhang, Yan-Jie (Research in astronomy and astrophysics, 2025)
In this paper, we perform a follow-up investigation of the solar eruption originating from active region 13575 on 2024 February 9. The primary eruption of a hot channel generates an X3.4 class flare, a full-halo coronal mass ejection (CME), and an extreme-ultraviolet (EUV) wave. Interaction between the wave and a quiescent prominence (QP) leads to a large-amplitude, transverse oscillation of QP. After the transverse oscillation, QP loses equilibrium and rises up. The ascending motion of the prominence is coherently detected and tracked up to  ∼1.68 R ⊙ by the Solar UltraViolet Imager onboard the GOES-16 spacecraft and up to  ∼2.2 R ⊙ by the Solar Corona Imager (SCI_UV) of the Ly α Solar Telescope onboard the ASO-S spacecraft. The velocity increases linearly from 12.3 to 68.5 km s −1 at 18:30 UT. The sympathetic eruption of QP drives the second CME with a typical three-part structure. The bright core comes from the eruptive prominence, which could be further observed up to  ∼3.3 R ⊙ by the Large Angle Spectroscopic Coronagraph onboard the Solar and Heliospheric Observatory mission. The leading edge of the second CME accelerates continuously from  ∼120 to  ∼277 km s −1 . The EUV wave plays an important role in linking the primary eruption with the sympathetic eruption.